Attenuation of dermal wounds through topical application of ointment containing phenol enriched fraction of Caesalpinia mimosoides Lam. - Bhat, Pradeep; Upadhya, Vinayak; Hegde, Ganesh R.; Hegde, Harsha V.; Roy, Subarna (Frontiers in Pharmacology, 2022)
Caesalpinia mimosoides Lam. is one of the important medicinal plants used by the traditional healers of Uttara Kannada district, Karnataka (India) for treating wounds. In our previous study ethanol extract of the plant was evaluated for its wound healing activity. In continuation, the present study was aimed to evaluate the phenol enriched fraction (PEF) of ethanol extract for wound healing activity along with its antioxidant, anti-inflammatory and antimicrobial properties. The potent wound healing activity of PEF was evidenced by observation of increased rate of cell migration in L929, 3T3L1 and L6 cells (92.59±1.53%, 98.42±0.82% and 96.63±0.61% respectively) at 7.81 µg/ml doses in assays carried out in vitro. Significantly enhanced rate of wound contraction (97.92±0.41%), tensile strength (973.67±4.43 g/mm2), hydroxyproline (31.31±0.64 mg/g) and hexosamine (8.30±0.47 mg/g) contents were observed on 15th post wounding day in 5% PEF treated animals. The enzymatic and non-enzymatic cellular antioxidants (superoxide dismutase, catalase and reduced glutathione) were upregulated (15.89±0.17 U/mg, 48.30±4.60 U/mg and 4.04±0.12 μg/g respectively) with the administration of 5% PEF. The significant antimicrobial, antioxidant and anti-inflammatory activities support the positive correlation of PEF with its enhanced wound healing activity. PEF contains expressive amounts of total phenolic and total flavonoid contents (578.28±2.30 mg GAE/g and 270.76±2.52 mg QE/g). Of the various chemicals displayed in RP-UFLC-DAD analysis of PEF, gallic acid (68.08 µg/mg) and ethyl gallate (255.91 µg/mg) were predominant. The results indicate that PEF has great potential for the topical management of open wounds.